x^2-2x-3>=0
D=4
x= -2+4/2=1
x2=-2-4/2=-3
проверим
(-oo;1] U [3;+oo)
x^2-2x-3-2a=x+3+a
x^2-3x-(3a+6)=0
D=9+4(3a+6)>0
9-12a+24>0
-12a+33>0
a>33/12
более одного корня то есть два
теперь
x^2-2x-3-2a=-x-a+3
x^2-x-a-6=0
D=1+4(a+6)>0
4a+25>0
a>-25/4
x^2-2x-3-2a=x+a+3
x^2 -3x- 3a-6=0
3a=x^2-3x-6
a=x^2/3-x-2
Если построить график то можно увидеть что при а=0
3ху-2х/у=28
-3ху+3х/у=-18
3ху-2х/у=28
решаем сложения
3х/у-2х/у=10
х/у=10
х=10*у
10*у*у- (10*у)/у=6
10у^2 - 10=6
10у^2=16
у^2=6
у= \|`6 у=- \|`6
х= 10\|`6 х=-10\|`6
ответ: (10\|`6;\|`6), (-10\|`6;-\|`6)